ПОДБОР ОПТИМАЛЬНЫХ ЗАЩИТНЫХ СРЕД ДЛЯ ДЛИТЕЛЬНОГО ХРАНЕНИЯ КУЛЬТУР МИКРООРГАНИЗМОВ В КРИОКОНСЕРВИРОВАННОМ ВИДЕ (Experimental biology, 2015)
Maintaining and expanding resources of industrial microorganisms relates to the priorities of biotechnology. Currently, there is a wide variety of protective media used for preservation of microorganisms. Selection of the optimal effective cryoprotectant is a very important aspect in the storage of microbial cultures in its frozen form.
Keywords: microorganism; cryoprotectant